Angels and Ingenues in Tennyson’s The Princess and Gilbert and Sullivan’s Princess Ida - Fasick, Laura (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractThis essay argues that Tennyson’s “The Princess,” frequently attacked as an anti-feminist poem, is more nuanced and potentially feminist than many critics have acknowledged. The poem’s exploration of gender roles emerges as especially challenging and thoughtful in comparison to the extreme gender conservatism of Gilbert and Sullivan’s musical parody, “Princess Ida.” Where Gilbert and Sullivan shrink all aspects of female character to sexual desire, Tennyson treats the female aspirations in his poem with considerable seriousness and respect. Ultimately, the reversion of the characters in “The Princess” to traditional gender roles seems based not upon fear of a new kind of femininity but upon fear of a new kind of masculinity. Tennyson’s poem implies that women can develop intellectually without threatening men’s stature, but men cannot develop emotionally and spiritually without losing worldly power. In that implication lies a tacit admission of the emptiness of Victorian society’s claims that women could wield power through moral authority. Moral authority, Tennyson implicitly confesses, has no real force in the world.